KEPERIDIAN DAN RASIO SEKS KETURUNAN KUMBANG AMBROSIA XYLEBORUS FERRUGINEUS YANG DIPELIHARA PADA MEDIA SERBUK LIMA JENIS KAYU1) - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1989)
Ambrosia   beetle  Xvleborus ferrugineus (Coleoptera:  Scolytidae)   was reared on sawdust  based artificial  media  of five wood  species,  i.e.  bireh(Betula sp.),.   elm  (Ulmus  americana), jack  pine   (Pinus sp.),   oak  (Quercus sp.),  and  an  unknown species.  Each  sawdust   media  was prepared   in  capped  test  tubes  and  one  female  beetle per  tube  was then  introduced.   The culture   media  were  incubated   in a  dark  room  at  28°C  and  70%  RH  for  40  days.The  result  showed   that  the  most  fecund   cultures,   by  mean  of  25.9  and  24.0  progenies  per  tube,   were  respectively produced    by  the  beetles  reared  on  the  elm  and  unknown  sawdust   diets.   The  moderate   fecundity,   producing   15.6  and 14.2 progenies  per tube,  was respectively   yielded   on  the  oak  and birch media,  and the less fecund  one,  9.4 progenies  each tube,  was that  on  the jack  pine  sawdust  diet.  The female  beetle  reared on the  entire diets yielded  progenies  with  a spanan- droua sex ratios ranging from  18.B   to 24.1  females per one  male.  There  is no dignificant  difference   among  the progeny's   sex ratios produced   by  the  beetle  reared on  the  various culture  media.